The Long and Short of Genetic Counseling Summary Letters: A Case–control Study. Issue 4 (14th December 2014) - Roggenbuck, J.; Temme, R.; Pond, D.; Baker, J.; Jarvis, K.; Liu, M.; Dugan, S.; Mendelsohn, N. J.
Abstract: Genetic counseling summary letters are intended to reinforce information received during genetic counseling, but little information is available on patient/family responses to these letters. We conducted a case–control study to assess the effectiveness of two different letter formats. Parents of children receiving a new diagnosis were enrolled. The control group ( n  = 85) received a genetic counseling summary letter in a narrative format, 4–5 pages in length. After the control enrollment period, genetic counselors were trained by a professional medical writer to develop a concise letter format. The case group ( n  = 64) received a concise letter, approximately 1.5 pages in length, utilizing simple sentences, lay terms, and lists/bullet points. Parents completed a survey 4 weeks after the visit to rate the letter's format, usefulness, and their emotional reaction. Results show that parents in the case group rated the letter more highly ( p  = 0.023), particularly in the emotional response dimension (rating changes in anxiety, depression, fear, ability to cope, and confidence in response to the letter). Parents in the case group also rated the genetic counseling session more highly ( p  = 0.039). In the control group, parents without a college degree were more likely to rate the letter as too long and the level of medical detail as too high. In the case group, no significant differences were seen between parents with or without a college degree. These data suggest that a short genetic counseling summary letter is rated higher by parents, and is particularly associated with a more positive emotional reaction. A short letter format highlighting the basic facts related to the genetic condition may be more useful to parents of diverse educational backgrounds, and may support a positive emotional adaptation at the time of a new diagnosis. Genetic counselors may benefit from specific instruction in medical and educational writing.